Studies of the Anti-Cancer Effects of Flavokawin B Onhuman Breast Cancer Cell Lines, Mcf7 And Mda-Mb-231 - Sinniah, Ajantha (2005)
A natural compound, Flavokawin B, isolated and purified from extract of Alpinia zerumbet was investigated for its anti-cancer properties on breast cancer cell lines, estrogen dependant MCF-7 and estrogen non-dependant MDA-MB-23. Tamoxifen, a non-steroidal anti-estrogen, primarily exploited as a drug against hormone-dependent breast cancer, acts as the positive control for this study. MCF-IOA, mammary epithelial cells serve as the negative control. The cytotoxicities of Flavokawin B and Tamoxifen on human breast cells were investigated using the MTT assay. The results showed that the ICSo @ S.E.M) value of Flavokawin B on MCF-7 cell line was determined to be 1 1.5 Ifi 0.01 5 pM/ml whilst the ICSo with Tarnoxifen was at 10.2 + 0.012 W m l . The ICS0 value of Flavokawin B on MDA-MB- 23 1 cell line was determined to be 17.5 + 0.0 19 pM/ml whilst the ICS0 value of Tamoxifen was at 32.5 2 4.2 pM/ml. The MTT assay results on normal epithelial cell line, MCF-1 OA treated with Flavokawin B demonstrated that the ICS0 value was 38.0 0.032 pM/ml whereas MCF-1OA treated with Tamoxifen had an ICSo value of 28 + 0.021 pM/ml. All values were statistically significant (p<0.05), as analysed using one sample T-test. The breast cancer cell lines treated at ICS0 concentration of both compounds before proceeding using confocal microscopy. There were no significant changes observed in the untreated cells. However, apoptotic features were that include membrane blebbing and nucleus condensation were evident at 24 hours. At 48 and 72 hours post treatment, convolution of nuclear membrane, destruction of nuclear membrane and fragmentation of the nucleus were observed. The TUNEL assay is designed to specifically detect and quantify apoptotic cells within a cell population, which primarily consists of both apoptotic and non-apoptotic cells. The TUNEL assay conducted showed that Flavokawin B induces more apoptosis on MCF-7 and MDA-MB-23 1 compared to Tamoxifen. In contrast, Flavokawin B has lesser lethal effects on MCF-1OA as compared to Tamoxifen. The levels of IL-6 secretion in MDA-MB-231 cell line decreased significantly after treatment with Flavokawin B. Immunofluorescence studies demonstrated that the levels of IL-6 secretion commensurate with the presence of membrane bound IL-6r when proliferation of the breast cells was inhibited during treatment with both the compounds. The MCF-7 and MDA-MB-23 1 cell lines were arrested at G1 phase when treated with both Flavokawin B and Tamoxifen. This shows that both the treatment follows similar mechanism to induce cell phase arrest. In conclusion, it could be confirmed that the pure compound Flavokawin B induces apoptosis in MCF-7 and MDA-MB-23 1 breast cancer cell lines contributing to the discovery of new alternative treatment strategy for breast cancer.